Environmental Risk Planning and Performance: A Public Healthcare Sustainability Balanced Scorecard Case Study - Salim Khaleel Khalid; Claire Beattie; John Sands; Gregory Jones (Australasian Accounting Business and Finance Journal, 2024)
This study explores how the sustainability balanced scorecard (SBSC) incorporates endogenous (actions created by an organisation) and exogenous environmental risk (actions or events external to an organisation) factors. The study's motivation is the traditional balanced scorecard’s (TBSC’s) limited ability to capture organisational environmental risks and resource resilience actions effectively. Public healthcare organisations' use of TBSC suggests its sensitivity to healthcare organisations’ external and internal environment changes, but with limited investigations. Data collected by interviews from a large Australian regional public health organisation were thematically analysed. The findings suggest SBSC is a more useful tool than TBSC in recognising and distinguishing a public healthcare system’s internally generated endogenous environmental practices, such as disposal of surgical waste products, and exogenous environmental risk factors including climate change impacts, natural disasters, and pandemics. The study provides two important contributions. First is a preliminary guide to identify and monitor actions that mitigate exposure to exogenous environmental risks and build resilience. Second, a new direction for the SBSC's theoretical development is identified by the findings, highlighting the use of the fifth perspective to monitor the response to exogenous conditions and resilience of the organisation to such risks.
Keywords: Sustainability Balanced Scorecard (SBSC); Balanced Scorecard (BSC); Public Healthcare; Environmental Risk; Climate Change; Performance Measures; BSC Four Perspectives; SBSC Five Perspectives